Investigating the Factors Influencing Students' Intention to Adopt e-Learning in a Small Island Developing State (SIDS) Economy: Evidence from Mauritius - Sannegadu, Rajesh; Seethiah, Dhruvandranah; Dookhony-Ramphul, Kiran; Gunesh, Raj; Seethiah, Krishnan; Jugessur, Heeranee (Lucian Blaga University, 2018)
This study is designed to investigate the factors influencing students’ intention to adopt electronic learning (e-learning) in a Small Island Developing State (SIDS) economy. The overarching theory underpinning this study is the Technology Acceptance Model (TAM) which has been extended to include the learner’s computer self-efficacy, the course flexibility and the instructor’s attitude dimensions. Constructs from this extended TAM were used to design a questionnaire that was administered among 494 students using a survey method. Relevant hypothesis were formulated and tested using multiple regression analysis. The results indicate that gender, type of course, Internet experience, prior experience in e-learning/mixed mode courses and initial proficiency level in e-learning significantly impacted on student’s intention to enroll for a fully online degree programme. Furthermore, computer self-efficacy, course flexibility and the instructor’s attitude were found to be pertinent antecedent to the Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) while (PEOU) and (PU) were both found to be predictors of attitude towards e-learning. These results have managerial implications for higher education institutions which need to pay a close attention to the factors influencing students’ attitude towards e-learning.